COMMODITY KNOWLEDGE IN THE PROCEDURES FOR IDENTIFYING GOODS FOR CUSTOMS PURPOSES - GYRKA, Olga; SAPOZHNIK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article deals with the issues of commodity expertise for customs purposes, taking into account the main task of commodity science to verify compliance of goods with the requirements of technical regulations and quality standards, which is important for protecting the interests of consumers and preventing the importation of dangerous or substandard goods. The purpose of the study was to investigate the role and importance of commodity knowledge and commodity science in the procedures for identifying goods for customs purposes and performing other customs formalities. It is shown that success in the classification of goods will be achieved by those customs specialists who will involve related knowledge in the field of commodity science and goods examination. When applying the Basic Rules for Interpretation of the HS, it is especially important to have a set of commodity expertise that provides for a thorough knowledge of the essence of export and import goods. The increase in the volume of trade, the emergence of goods with new properties and various combinations of them significantly complicate their adjustment to the established classification groups in the HS and the HS built on its basis. Difficulties arising from classification increase the need for the use of specialized knowledge (consultations, research, expertise). The need for customs control over the correctness of classification requires continuous improvement of the customs service's expert support system, financial costs for the purchase of equipment, development of special research methods, training of highly qualified personnel, etc. The author examines the structure of the HS and the principles of allocation of a separate group, position or subheading in the international nomenclatures for a product and the reasons for allocation of such HS groups as 21, 38, 63, 83, 96, since these groups contain a large number of different products regardless of their chemical composition, type of material, nature of origin. At the same time, customs statistics indirectly indicate the level of significance of such goods in the international market and are taken into account when revising the HS nomenclature and making changes to it every 5 years. The author concludes that effective state regulation of export and import of goods requires practical developments (methods, algorithms, recommendations, etc.) for identifying and controlling the accuracy of the declared HS code. When developing them, in addition to the classification criteria adopted in the HS (material of manufacture, purpose, nature of origin, depth of processing, etc.), it is necessary to take into account a comprehensive criterion characterizing the material essence of the goods and the totality of their consumer properties.
Keywords: commodity nomenclature of foreign economic activity; classification of goods for customs purposes; customs classification; customs law; customs business; customs legislation